2005
DOI: 10.1007/s00412-005-0339-3
|View full text |Cite
|
Sign up to set email alerts
|

Chriz, a chromodomain protein specific for the interbands of Drosophila melanogaster polytene chromosomes

Abstract: Polytene interphase chromosomes are compacted into a series of bands and interbands reflecting their organization into independent chromosomal domains. In order to understand chromosomal organization, we set out to study the role of proteins that are selective for interbands. Here we describe the Drosophila melanogaster chromodomain protein Chriz that is coimmunoprecipitated with the zinc finger protein Z4. Both proteins colocalize exclusively to the interbands on Drosophila polytene chromosomes. Like Z4, Chri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 63 publications
4
59
1
Order By: Relevance
“…Chromatin proteins that bind at the endogenous 61C7-8 locus are also bound at the new position. We observed prominent binding of Chriz, Z4 (data not shown) and Jil-1, proteins that are typically found in decondensed chromatin as reported previously (Eggert et al, 2004;Gortchakov et al, 2005;Wang et al, 2001). Chriz and Jil-1 physically interact (Rath et al, 2006), and on Chriz knockdown both Jil-1 chromosomal binding and H3S10 phosphorylation are dramatically reduced, indicating that Chriz is required for chromosomal targeting of Jil-1 (Gan et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Chromatin proteins that bind at the endogenous 61C7-8 locus are also bound at the new position. We observed prominent binding of Chriz, Z4 (data not shown) and Jil-1, proteins that are typically found in decondensed chromatin as reported previously (Eggert et al, 2004;Gortchakov et al, 2005;Wang et al, 2001). Chriz and Jil-1 physically interact (Rath et al, 2006), and on Chriz knockdown both Jil-1 chromosomal binding and H3S10 phosphorylation are dramatically reduced, indicating that Chriz is required for chromosomal targeting of Jil-1 (Gan et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…A set of proteins mainly recruited to interband chromatin might play a role in open chromatin formation. Besides paused forms of RNA polymerase II, these include nucleosome-remodeling and histone-modifying proteins like Brahma, TRX and the H3S10 kinase Jil-1 (Wang et al, 2001), insulator proteins like BEAF32AB, CP190 and the Drosophila homolog of CTCF (dCTCF) (Van Bortle and Corces, 2012) and proteins of as yet unknown function, like Chriz (also known as Chro) (Gortchakov et al, 2005;Rath et al, 2006) and Z4 (also known as Pzg) (Eggert et al, 2004). Furthermore, interband chromatin is enriched for 'activating' chromatin modifications, like acetylation (H4K16ac and H3K9ac), methylation (H3K4me3) and phosphorylation (phospho-H3S10) Demakov et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, localization of Chromator to polytene interbands suggests it also has a functional role in maintaining chromatin structure during interphase. Such a role is supported by the finding of Eggert et al (Eggert et al, 2004) that Chromator (which these workers refer to as Chriz) is found in a protein complex together with the interband-specific zinc-finger protein Z4 (Eggert et al, Interactions between JIL-1 and chromator Gortchakov et al, 2005). That Z4 participates in regulating polytene chromosomal structure is likely because Z4-null mutant chromosomes show a decompaction of chromatin and a loss of a clear band/interband pattern (Eggert et al, 2004).…”
Section: Introductionmentioning
confidence: 93%
“…That Z4 participates in regulating polytene chromosomal structure is likely because Z4-null mutant chromosomes show a decompaction of chromatin and a loss of a clear band/interband pattern (Eggert et al, 2004). However, the effect of Chromator on polytene chromosome morphology has been difficult to study because null alleles of Chro die as embryos or first-instar larvae before salivary gland polytene chromosomes can be analyzed (Rath et al, 2004;Gortchakov et al, 2005). For this reason we performed an EMS mutagenesis screen that generated two new Chro hypomorphic alleles.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to dHP1c, WOC and ROW, these experiments detected the dHP1b isoform 34 ; the boundary protein BEAF- 32 (ref. 35); the chromosomal proteins Chromator and Z4, which are known to form a complex 36,37 ; the RNA-binding protein Blanks 38 ; the ubiquitin receptor protein dDsk2; and coilin, a factor that marks Cajal bodies and associates to the histone locus 39 . Co-IP experiments directly confirmed several of these interactions.…”
mentioning
confidence: 99%